Anemia from A to zinc: Hypocupremia in the setting of gastric bypass and zinc excess - Vineeth Tatineni; Julie Y. An; Matthew R. Leffew; Sameer A. Mahesh (Clinical Case Reports, 2020)
Abstract Hypocupremia can result in a bi‐lineage deficiency of leukocytes and erythrocytes. Although commonly seen from gastrointestinal malabsorption, hypocupremia can be further exacerbated with excessive zinc intake causing increased fecal copper excretion. Dietary supplementation is prevalent in the outpatient setting and must be considered as a possible source of hematologic pathologies.